Epiphyseal fractures of the distal humerus - De Jager, L T (Department of Health and Rehabilitation Sciences, 2017)
This dissertation discusses distal humeral epiphyseal injuries in children, i.e. lateral condylar fractures, medial condylar fractures, fracture-separation of the distal humeral epiphysis and T-condylar fractures. Medial and lateral epicondylar fractures, being apophyseal, are excluded. The research was done at the Red Cross Children's Hospital Trauma Unit. It was based on two clinical retrospective studies and one case report: a: 60 lateral condylar fractures presenting from 1984 to 1987 -were reviewed. b: 12 fracture-separations of the distal humeral epiphysis presenting from 1984 to 1989 were reviewed. c: One case report of a medial condylar fracture with associated elbow dislocation The distal humeral epiphysis is the second most commonly injured epiphysis in the body, after that of the distal radius (Peterson 1972). Supracondylar fractures are the most common fractures around the elbow in children, making up 65% of the total (Canale 1987). Lateral condyle fractures have an incidence of 17.4%, compared to 3.2% for medial condylar fractures and 0.8% for T-condylar fractures (Canale 1987). At the Red Cross Children's Hospital, 60 displaced supracondylar fractures, 20 lateral condylar fractures and 2 to 3 fracture-separations of the distal humeral epiphysis are seen every year. Medial condylar fractures are rare.